Comparative study on meristem culture of three potato cultivars diamant, cardinal and granula and their shoot formation (Asian Journal of Medical and Biological Research, 2016)
The main aim of this study was to analyze the comparative study on meristem culture of three important potato cultivars, diamant, cardinal and granula and their shoot formation using meristem tips. Apical meristems were isolated from shoot tips of 25-35 days old field grown plants. After surface sterilization the meristems (0.3 mm) were isolated from the shoot tips. After isolation the apical meristems were placed quickly on M shaped filter paper bridge in culture tubes containing liquid MS medium supplemented with various concentrations and combinations of different plant growth regulators. Meristems showed their first growth response by increase in size and became greenish white in colour. They continued their growth and developed shoots with roots. In the present investigation, among the three cultivars of potato, cardinal were the best responsive cultivars for the resuming new growth of cultured meristems on MS medium supplemented with KIN (0.4 mg l-1) + GA3 (0.5 mg l-1). Cultivar diamant showed comparatively better growth response in the primary culture and granula showed better results in shoot length formation in MS0 medium. Cultivar cardinal proved to be best potato cultivar in case of meristem culture than diamant and granula cultivars.Asian J. Med. Biol. Res. December 2015, 1(3): 537-544